Resternotomy in children with congenital heart disease - management algorithm applied in the Department of Cardiothoracic Surgery in Children's Memorial Health Institute in Warsaw - Radoslaw Jaworski; Andrzej Kansy; Mariusz Birbach; Andrzej Pastuszko; Krzysztof Mozol; Michal Kozlowski; Aleksandra Wasiak; Piotr Burczynski; Bohdan Maruszewski (Termedia Publishing House, 2020)
The paper summarizes key problems related to resternotomy in children with congenital heart defects which were discussed during the 9th Congress of the Polish Society of Cardiothoracic Surgeons 2018 in Szczecin. An attempt was made to address various aspects of the issue in order to systematize the available knowledge and minimize the risks associated with reoperations in this particular group of patients. Additionally, the paper presents the algorithm for diagnostic and therapeutic management applied in children considered eligible for resternotomy in the Department of Cardiothoracic Surgery in Children's Memorial Health Institute in Warsaw.